ANALYZE FACTORS THAT CAN PREVENT COMPLICATIONS POST - OPERATIVE HYPOSPADIA : A SCOPING REVIEW - Saepudin, Aceng; Rakhmawati, Windy; Ramdhanie, Gusgus Ghraha (Universitas Aisyah Pringsewu, 2024)
Background: Hypospadias can be identified by the abnormal location of the child's penis opening, the location depends on the type of hypospadias, surgery is an effective measure but cannot be separated from the risk of complications. Objective: to identify literature related to complications after hypospadias surgery and factors to prevent complications. Methods: this review used a search through databases; PubMed, Spingerlink, CINAHL, ScienceDirect and using the Google Scholar search engine. The conceptual framework uses PRISMA-SCR to select and categorize data. The results obtained were N=9,354 articles, there were 11 articles entered, selected and meeting the criteria, namely qualitative and quantitative articles, published from 2010 to 2022, from various countries and in English. The results of the analysis showed various complications after hypospadias surgery as well as efforts to prevent complications, including: 1 study preventing surgical wound infections, 9 studies selecting surgical techniques to prevent several complications, 1 study preventing complications by considering age. Conclusion: from the review of this article, it was found that post-operative hypospadias complications can be prevented by cleanliness of the surgical area, choosing the right surgical technique, and considering the child's age for surgery . Key words: children, complications, post surgery , hypospadias